The effect of different SiO2/Al2O3 ratios of HZSM-5 on the conversion of palm oil to liquid fuels - Saidina Amin, Nor Aishah; Kasim, Farizul Hafiz (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Palm oil can be converted to liquid fuels by catalytic cracking process. The present effort studies the conversion of palm oil vapors to liquid hydrocarbon fuels over HZSM-5 zeolite with different SiO2/Al2O3 ratios. The direct synthesis of HZSM-5 zeolite with SiO2/Al2O3 ratios is reported in this paper. The characterization of the catalyst is performed using X-Ray diffraction(XRD) an Fourier transform infrared (FTIR). The catalyst activity test is conducted in a micro-packed bed reactor via a continuous system mode. The catalyst is loaded in the middle of the reactor and supported with glass wool. Nitrogen gas is used to flush the system before and after the experiment. The products were analyzed using gas chromatograph. From the experimental result, the conversion of palm oil over HZSM-5 with SiO2/Al2O3=30 demonstrated a high percentage of gasoline compared to the other samples.